2005
DOI: 10.1096/fj.04-3180fje
|View full text |Cite
|
Sign up to set email alerts
|

Green fluorescent protein is a quantitative reporter of gene expression in individual eukaryotic cells

Abstract: Green fluorescent protein (GFP) has gained widespread use as a tool to visualize spatial and temporal patterns of gene expression in vivo. However, it is not generally accepted that GFP can also be used as a quantitative reporter of gene expression. We report that GFP is a reliable reporter of gene expression in individual eukaryotic cells when fluorescence is measured by flow cytometry. Two pieces of evidence that support this conclusion are that 1. GFP fluorescence increases in direct proportion to the GFP g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
122
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(131 citation statements)
references
References 49 publications
4
122
0
5
Order By: Relevance
“…1C). The use of GFP as a precise and quantitative reporter for gene expression is well documented in the literature, 43,44 and the relative abundances we determined are in good agreement with those determined using epitope tags 45 (correlation coefficient D 0.92). We confirmed our ability to detect changes in chaperone expression using this approach by comparing GFP intensity at 30 C and following heat shock (Ssa, Hsp104, Ydj1 and Sis1 exhibit increased expression after heat shock while Ssb exhibits a modest decrease; not shown).…”
Section: The Rac Antagonizes Induced and Spontaneous Formation Of Thesupporting
confidence: 82%
“…1C). The use of GFP as a precise and quantitative reporter for gene expression is well documented in the literature, 43,44 and the relative abundances we determined are in good agreement with those determined using epitope tags 45 (correlation coefficient D 0.92). We confirmed our ability to detect changes in chaperone expression using this approach by comparing GFP intensity at 30 C and following heat shock (Ssa, Hsp104, Ydj1 and Sis1 exhibit increased expression after heat shock while Ssb exhibits a modest decrease; not shown).…”
Section: The Rac Antagonizes Induced and Spontaneous Formation Of Thesupporting
confidence: 82%
“…15 Recently, it was demonstrated that GFP also had all the essential properties of a quantitative Lentivirus with enhanced neuron-specific promoters H Hioki et al reporter protein and concluded that GFP is reliable and useful one for analysis of promoter activity by measuring fluorescence intensity. 16 As GFP has the advantage that promoter activity can be easily monitored in single cells in sections, we selected GFP as a reporter protein in the present study.…”
Section: Technical Consideration: Quantification Of Promoter Activitymentioning
confidence: 99%
“…One decade relative fluorescent unit (RFU) was set as threshold. Data were analyzed with WinMDI (version 2.8) software to obtain the percentage of the GFP positive cells and G mean values (Ducrest et al, 2002;Soboleski et al, 2005).…”
Section: Flow Cytometry Analysismentioning
confidence: 99%